Labour Turnover in the Hospitality Industry - Pranoto, Ersan Suria (Bina Nusantara University, 2011)
Labour turnover are inevitable and many businesses and industries are dealing with this issue every single day. It is also a great issue in the Hospitality Industry, the intensity were varies according to the size of the establishment, some are low and many is as high as the height of their buildings. The fact also stated that workers in the hospitality industry in the early stage of their career expect to move from one job to another, creating a very low desirability of steady workplaces and the job security. Moreover, the labour turnover is very much increases when employees are far more specialised, more difficult to find and requires more training. Therefore, it is in the best interests of hospitality managers to understand the causes and the effects of turnover so that they may reduce its costs.